Mental health and coping strategies among international health science students during the COVID-19 pandemic: A cross-sectional study - Nair, Ambili; Fatch, Kalembo; Huaqiong, Zhou; Ng, Linda; Glenda, Hawley; Grogan, Aaron; Ng, Leo; Chen, Wai; Lim, Eric (Elsevier, 2023)
Background: Amidst the challenges brought about by the COVID-19 pandemic, international students face significant mental health burdens. Aim: This study aimed to explore international health science students’ mental health and coping abilities during the coronavirus disease 2019 pandemic. Methodology: A survey was conducted between May and September 2022 using an online questionnaire with the Kessler Psychological Distress Scale and Coping Self-Efficacy Scale. Findings: A total of 105 international students from 3 Australian universities were recruited with 84% of the participants being nursing students. There was no comparison group of local/Australian-born students. Psy chological distress was reported by 67% of respondents. Problem-focused coping prevailed with higher scores than emotional-focused and social support coping. Financial struggles with rent increased psychologi cal distress likelihood, while social support mitigated it. Social support coping was significantly associated with psychological distress, clinical placement, and problem-focused and emotional-focused coping. Emo tional-focused and Problem-focused coping was associated with participants’ age. Discussion: The study underscores the need for affordable housing and support networks while recognizing the interdependence of coping dimensions for enhancing students' overall well-being